A Clinical Study to Evaluate the Efficacy of Haridrakhanda in the Management of Allergic Rhinitis in Paediatric Age Group (International Journal of Ayurveda and Pharma Research, 2022)
Increased levels of environmental pollution, especially air pollution due to industrialization, increased vehicles, re-suspended dust on roads due to vehicle movement and construction activities, open waste burning, combustion of various fuels and also seasonal influences from dust storms, forest fires, open field fires during harvest season, sea salt near coastal areas and decreased immunity due to factors like lifestyle modifications, food habits and climatic variations leads to innumerable health hazards. Among those one such condition is Vataja Pratishyaya with a similar clinical entity with that of allergic rhinitis. Allergy is a condition in which the immune system reacts abnormally to a foreign substance. ‘Allergic rhinitis’ is characterized by inflammatory changes in the nasal mucosa caused by exposure to inhaled allergens. This is highly prevalent and common disease to the extent that 30% of the total diseases and around 20-30% of the Indian population suffers from the same. Allergic rhinitis is associated with number of co morbid conditions such as asthma, sinusitis, otitis media, atopic dermatitis and nasal polyps. The condition shows immediate hypersensitivity reaction of Nasal mucosa to allergens like pollen, dust, strong perfumes, smoke and cold climate. Pratishyaya is well known for its re-occurrence and chronicity. In this study Haridrakhanda was given internally for the management of Allergic rhinitis in children of 6 to 14 years of age group. Milk was given as anupana by considering the properties of drugs in the formulation and palatability in children. Subjective and objective parameters [according to ‘Total Nasal symptom score’, North West ENT and Allergy] were assessed and the results obtained were statistically significant.